Harmonizing Faith and Care: Analyzing Inpatient Satisfaction in Islamic Healthcare at Unimus Hospital, Indonesia - Ashidiqi, Aswin Imam; Shariff, Shaharom; Kusbaryanto, Kusbaryanto (Universitas Muhammadiyah Yogyakarta, 2025)
Islamic hospitals aim to integrate religious values with healthcare delivery, ensuring services align with both medical standards and Shariah principles. The study analyzes the impact of Islamic service dimensions on inpatient satisfaction at Unimus Hospital, focusing on compliance, reliability, responsiveness, assurance, empathy, and tangibles, using SERVQUAL, CARTER, and PAKSERV models. A mixed-method approach with a sequential explanatory design was applied, integrating quantitative and qualitative research. The quantitative phase involved a cross-sectional survey of 94 inpatients, selected through total sampling, using a structured questionnaire validated through instrument testing, including Pearson correlation for validity and Cronbach’s alpha (≥0.6) for reliability. The qualitative phase employed purposive sampling, engaging six key informants through semi-structured interviews to explore patient experiences and service challenges. Data analysis included descriptive statistics for quantitative findings, while Miles and Huberman’s interactive model was applied for qualitative data. Methodological and data triangulation ensured validity by integrating multiple data sources and analytical methods. Findings indicated that 88.5% of patients reported high satisfaction, yet 1.06% expressed dissatisfaction regarding compliance, reliability, and responsiveness, citing delays in medical services, inconsistencies in religious support, and limited implementation of Shariah-based healthcare protocols. Strengthening staff training, religious service consistency, and hospital infrastructure could enhance patient trust and satisfaction. The study contributes empirical insights for Islamic healthcare management, supporting policy refinement and service improvements in faith-based hospitals.